Identifying a type of toxic effectors exported by the type VII secretion system to enhance competitive fitness in Streptococcus suis - Bai, Qiankun; Liu, Jianan; Zhao, Jie; Pan, Xinming; Zhang, Yue; Wu, Zongfu; Ma, Jiale (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundStreptococcus suis poses a significant threat to both pig farming and public health, causing severe disease such as septicemia and meningitis. The type VII secretion system (T7SS) delivers toxic effectors to play a crucial role in interbacterial competition and is vital for the zoonotic pathogen S. suis to colonize host tonsils effectively.ResultsHere, we identified a type of hypothetical T7SS effector in S. suis, which appears to be fragmented toxins lacking the N-terminal YeeF domain, redesignated as MSE-ExTs. MSE (marker for searching effectors) is a conserved sequence at the N-termini of modular effectors showing a diverse range of toxicities targeting NAD +. Cognate WXG100-like and full-length EssC proteins contribute to activate the T7SS secretion. While most MSE-ExTs (MSE-fusing exported toxins) are encoded downstream of a truncated essC and lack cognate WXG100-like genes, they are nonetheless exported and function in interbacterial antagonism, thereby conferring a competitive advantage against bacterial isolates derived from tonsil microbiota. Deletion of the truncated essC could not diminish the MSE-ExT1 delivery, while the full-length EssC1 encoded in T7SS core locus was required for the lethality of MSE-ExT1 to sensitive bacterial cells. MapC2, an upstream small helical protein, shares a nearly identical C-terminal 50-amino acid (aa) sequence with EIC-CR (C-terminal conserved region of effector-paired immunity protein). This conserved fragment harbors a “YxxxD” targeting signal and interacts with the D1 ATPase domain of the non-neighboring EssC, thereby activating the secretion of MSE-ExTs.ConclusionsThis alternative strategy facilitates effectors’ delivery, even for fragmented substrates, highlighting its importance in ensuring the functionality of T7SS.